Is the Arctic really a frontier? Settlement dynamics within various Arctic Limits based on the Arcticapolis geohistorical database - Vaguet, Yvette; Ourng, Chanvoleak; Moriconi-Ebrard, François (Espace populations sociétés, 2021)
International audience